Characterization of Antimicrobial Peptides toward the Development of Novel Antibiotics - Wataru Aoki; Mitsuyoshi Ueda (Pharmaceuticals, 2013)
Antimicrobial agents have eradicated many infectious diseases and significantly improved our living environment. However, abuse of antimicrobial agents has accelerated the emergence of multidrug-resistant microorganisms, and there is an urgent need for novel antibiotics. Antimicrobial peptides (AMPs) have attracted attention as a novel class of antimicrobial agents because AMPs efficiently kill a wide range of species, including bacteria, fungi, and viruses, via a novel mechanism of action. In addition, they are effective against pathogens that are resistant to almost all conventional antibiotics. AMPs have promising properties; they directly disrupt the functions of cellular membranes and nucleic acids, and the rate of appearance of AMP-resistant strains is very low. However, as pharmaceuticals, AMPs exhibit unfavorable properties, such as instability, hemolytic activity, high cost of production, salt sensitivity, and a broad spectrum of activity. Therefore, it is vital to improve these properties to develop novel AMP treatments. Here, we have reviewed the basic biochemical properties of AMPs and the recent strategies used to modulate these properties of AMPs to enhance their safety.